EDUKASI TENTANG PENANGANAN CEDERA AKUT PADA ANAK DENGAN METODE PRICE PADA GURU PENDIDIKAN ANAK USIA DINI - Teju, Selly Omega Dila; Lestarina, Ni Nyoman Wahyu; Suadnyani, Ni Ketut (Universitas katolik Musi Charitas, 2025)
Purpose: This community service activity aimed to enhance early childhood education teachers’ knowledge and skills in handling acute injuries in children using the PRICE method (Protection, Rest, Ice, Compression, Elevation). The goal was to provide practical and preventive health education tailored for school-based injury response. Design/Methodology/Approach: The activity was carried out through direct education and demonstration sessions involving early childhood education teachers in Surabaya. Educational media, including posters and leaflets, were used to deliver the material. Demonstrations were conducted to simulate the application of the PRICE method in handling common school injuries. Findings: The results showed a significant improvement in participants’ understanding of acute injury management. Teachers actively engaged in the simulation and expressed increased confidence in applying the PRICE method when injuries occur in school environments. Practical Implications: This training is expected to improve the readiness of school staff to respond to minor injuries, thereby reducing potential complications and promoting child safety in early education settings. Originality/Value: The activity contributes to increasing health literacy among non-medical education professionals. It bridges the gap between theory and practice in first aid for children, especially in environments with limited access to immediate medical assistance.